2018
DOI: 10.3390/s18103544
|View full text |Cite
|
Sign up to set email alerts
|

Trends and Advances in the Characterization of Gas Sensing Materials Based on Semiconducting Oxides

Abstract: The understanding of the fundamental properties and processes of chemoresistive gas sensors based on semiconducting metal oxides is driven by the available characterization techniques and sophisticated approaches used to identify structure-function-relationships. This article summarizes trends and advances in the characterization of gas sensing materials based on semiconducting metal oxides, giving a unique overview of the state of the art methodology used in this field. The focus is set on spectroscopic techn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(23 citation statements)
references
References 77 publications
0
23
0
Order By: Relevance
“…Some authors also observed the poor response that shows some semiconductors at low temperatures (in our case at 100 °C), such as ours. They attributed such phenomenon to the fact that the oxygen species present (usually [ 2 ]) do not react with the test gas nor with the pellets’ surface (that is, adsorption and desorption processes do not occur) [ 5 , 10 , 12 , 17 ], provoking the absence of changes in the material’s electrical resistance [ 5 , 36 ] (see Figure 10 ). On the contrary, when increasing the operating temperature to 200 and 300 °C, a very significant increase in the response of the pellets was recorded (see Figure 10 a,b).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Some authors also observed the poor response that shows some semiconductors at low temperatures (in our case at 100 °C), such as ours. They attributed such phenomenon to the fact that the oxygen species present (usually [ 2 ]) do not react with the test gas nor with the pellets’ surface (that is, adsorption and desorption processes do not occur) [ 5 , 10 , 12 , 17 ], provoking the absence of changes in the material’s electrical resistance [ 5 , 36 ] (see Figure 10 ). On the contrary, when increasing the operating temperature to 200 and 300 °C, a very significant increase in the response of the pellets was recorded (see Figure 10 a,b).…”
Section: Resultsmentioning
confidence: 99%
“…The wet chemistry processes have allowed reducing the particle size to a nanometric scale, thus favoring the increase of both the surface area and the physical and chemical properties of the material [ 9 ]. The nanometric size of the particles increases their electrical response, in addition to the improvement of their magnetic, optical, and catalytic properties [ 10 , 11 ]. All this implies that materials with nanometric particle size can potentially be applied as gas sensors [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…70,71 A large number of operando methods have been developed to examine SOFC/SMOX. [72][73][74] In the field of SMOX based gas sensing, operando x-ray adsorption spectroscopy is used to study the oxidations state and structural parameters of surface additives on the interaction with the surrounding atmosphere. 75,76 Operando vibration spectroscopy, both Raman and diffuse Please do not adjust margins Please do not adjust margins reflectance infrared Fourier transform (DRIFT) are widely used to look at the surface chemistry of SMOX based gas sensor and have recently been used to examine fuel cells.…”
Section: Spectroscopymentioning
confidence: 99%
“…There are three common materials used as sensing elements: metal oxide semiconductor (MOS) [23], conductive polymer composites (CPCs) [24], and carbon nano-materials [25].…”
Section: Gas Sensors Array and Signal Preprocessingmentioning
confidence: 99%